DETERMINANTS OF EFFECTIVE BALANCED SCORECARD IMPLEMENTATION IN THE INDONESIAN FMCG INDUSTRY: A SYSTEMATIC LITERATURE REVIEW - Luluk Adinda Safitri; Intan Ayu Setiyani; Dhira Alifah Nazahra Putri; Adhelia Putri Paramita; Dwi Firdayani; Ninuk Riesmiyantiningtias (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2025)
The increasing complexity of today's business environment requires organizations to adopt comprehensive performance measurement systems that integrate both financial and non-financial dimensions. Although the Balanced Scorecard (BSC) has been widely implemented as a strategic performance management framework, previous studies have reported inconsistent implementation outcomes across organizations, particularly within Indonesia's Fast Moving Consumer Goods (FMCG) industry. This inconsistency indicates a limited understanding of the determinants influencing the effectiveness of Balanced Scorecard implementation. Therefore, this study aims to identify the determinants of effective Balanced Scorecard implementation in the Indonesian FMCG industry through a Systematic Literature Review (SLR). The study synthesized empirical evidence from previous research published between 2021 and 2025, focusing on two leading Indonesian FMCG companies, PT. Indofood CBP Sukses Makmur Tbk and PT. Unilever Indonesia Tbk. Relevant studies were collected from Google Scholar and ResearchGate and analyzed using a comparative qualitative synthesis based on the four Balanced Scorecard perspectives: financial, customer, internal business processes, and learning and growth. The findings reveal that the effectiveness of Balanced Scorecard implementation is primarily influenced by four determinants: the comprehensiveness of performance measurement indicators, operational efficiency and internal resource management, customer value creation and market responsiveness, and employee productivity and organizational learning capability. Overall, PT. Indofood CBP Sukses Makmur Tbk demonstrated more consistent performance across all Balanced Scorecard perspectives than PT. Unilever Indonesia Tbk. This study contributes to the strategic performance management literature by synthesizing empirical evidence on the determinants of effective Balanced Scorecard implementation and provides practical guidance for organizations seeking to strengthen integrated performance measurement systems.